An integrative framework on the impact of allies: How identity‐based needs influence intergroup solidarity and social movements. (11th August 2020) - Selvanathan, Hema Preya; Lickel, Brian; Dasgupta, Nilanjana
Abstract: What impact do advantaged group allies have within social movements? Although solidarity between advantaged and disadvantaged group members is often encouraged to achieve long‐term social change, allies run the risk of being ineffective or counterproductive, therefore making it important to shift our focus towards understanding the impact of allies. We propose an integrative theoretical framework describing the positive and negative impact of allies based on their distinct identity‐based needs: advantaged group members' need for moral acceptance and disadvantaged group members' need for empowerment and respect. By consolidating extant literature and identifying gaps in prior research, we propose a set of hypotheses concerning (a) tensions that arise within intergroup solidarity efforts for social change between advantaged group allies and disadvantaged group members, and (b) the role of allies in influencing broader public opinion to advance the psychology of social change.